A new blind anti‐jamming algorithm based on a novel antenna array design - Yang, Xin; Wang, Feixue; Liu, Wenxiang; Chen, Feiqiang (IET radar, sonar & navigation, 2022)
The next‐generation navigation tools are developed to enable precision and reliability. Military users are more likely to encounter jamming, so it is necessary to seek the technologies which can steadily provide high‐precision positioning services in all‐weather and harsh conditions. However, when users use an array antenna for interference suppression, it usually introduces pseudorange and carrier phase biases, which deteriorates the accuracy and integrity of positioning. To address this issue, the authors propose a blind anti‐interference algorithm with biases suppression. Compared to the commonly used blind space–time adaptive anti‐jamming algorithms, this algorithm can not only retain the advantages of the simple structure of the blind anti‐jamming algorithm but also suppress pseudorange biases and carrier phase biases, both of which are crucial for users to obtain the availability of positioning. Moreover, the algorithm proposed can be applied easily and quickly to the actual high‐precision positioning system with minor hardware changes in some cases. The relevant theoretical analysis and experiments have proved the effectiveness of the proposed algorithm: (1) code phase biases and carrier phase biases can almost be ignored and (2) it also can significantly improve the accuracy and integrity of positioning; the average positioning error is 1.6 mm, and it can keep the positioning accuracy better than 0.1 m for 97.5% of the time.